SOGUK SAVAS SONRASI DÖNEMDEN GÜNÜMÜZE ABD'NIN ASYA PASIFIK STRATEJISI - Durmus, Zeynal Abidin (Özgür TÜFEKÇI, 2023)
Uluslararasi arenadaki güç mücadelelerinin yasandigi en önemli alanlardan biri de süphe yok ki Asya-Pasifik Bölgesi'dir. Son otuz yilda bu bölgede gelisen hizli ekonomik büyüme neticesinde evrensel ekonomik ve politik agirlik Atlantik'ten, Pasifik bölgesine tasinmistir. Bu bölgede ABD, Çin, Japonya ve Hindistan gibi önemli aktörler arasindaki rekabet giderek hiz kazanmistir. Tüm bu gelismeler, ABD'nin ilgisini bu bölgeye çekmistir. Bu makalenin birinci bölümünde Asya Pasifik Bölgesi tanitilarak bu bölgede, bölgesel ve küresel güvenligi tehdit eden konular ele alinmistir. Çalismanin ikinci bölümünde Asya Pasifik Bölgesinin ABD açisindan önemi ve bölgeye yönelik politika hedefleri, ABD'nin Asya-Pasifik stratejisinin temelleri ve Soguk Savas sonrasi ABD'nin Asya-Pasifik politikasi anlatilmaya çalisilmistir. Makalenin devaminda ise ABD'nin Hint-Pasifik kavramina yaklasimi ve bu baglamda gelistirdigi güvenlik antlasmalari ele alinmistir.

There is no doubt that one of the most important areas where power struggles occur in the international arena is the Asia-Pacific Region. As a result of the rapid economic growth in this region in the last thirty years, universal economic and political weight has moved from the Atlantic to the Pacific region. In this region, competition between important actors such as the United States of America (USA), China, Japan, and India has accelerated. All these developments attracted the attention of the USA to this region. This article has been prepared by making use of scientific books, articles and international documents. The aim of the article is to reveal the strategies followed by the USA towards the Asia Pacific region, whose importance has increased internationally in recent years. In this context, in the first part of this article, the Asia Pacific Region is introduced, and the issues that threaten regional and global security in this region are discussed. In the second part of the study, the importance of the Asia-Pacific Region for the USA and its policy objectives for the region, the foundations of the USA’s Asia-Pacific strategy and the USA’s Asia-Pacific policy after the Cold War were tried to be explained. In the rest of the article, the USA’s approach to the Indo-Pacific concept and the security agreements developed in this context are discussed.
The USA’s Asian Pacific Strategy from the Post-Cold War Period to the Present
Keywords: American Studies; Amerika Çalismalari; Studies of Asian Society; Asya Toplumu Çalismalari